Girish Karnad`s plays: performance and critical perspectives - Tutun Mukherjee Ed (Pencraft International, 2006)
Contributed articles on the Kannada plays of Girish Ragunath Karnad, b. 1938, playwright, director, and actor from India; includes articles on the performances of his plays and his interview.